Factors Affecting Elderly Doubt in Receiving Vaccines COVID-19 in the New Normal Era in Maccini Village, Makassar District - Nurul Rahmaniar Amalia Nurul (Media Publikasi Cendekia Indonesia, 2023)
Currently, Indonesia is in the process of transitioning from a pandemic to an endemic one. One of the steps to break the chain of transmission of COVID-19 is to implement a COVID-19 vaccination program. Vaccination was started in Indonesia on January 13, 2021 by President Joko Widodo, then followed by vaccination of priority groups such as health workers, the elderly and all Indonesian people. There are still many who doubt that vaccines can inhibit COVID-19, one of which is the elderly group. The purpose of the study was to determine the factors that influence the doubts of the elderly in receiving the COVID-19 vaccine in the new normal era in Maccini Village, Makassar District. This research is a descriptive study with a purposive sampling technique, then to obtain research data using an offline questionnaire consisting of 29 questions. Data analysis is descriptive analysis using Ms. excel. The seven factors that influence the elderly's doubts, the highest factor with a value of 71.2% is the past history factor and the lowest factor with a value of 23.5% is geographical barriers and costs. The average of the seven factors is 39.8% and is included in the less category. The elderly in Maccini Village, refused to be vaccinated against COVID-19, even from 95 respondents, none of them were willing to be vaccinated against COVID-19, with the highest reason being that with a score of 62.1%, having comorbidities was prohibited by doctors